Analisis Manajemen Layanan Penerimaan Siswa Baru Menggunakan Framework ITIL Versi 3 Pada Domain Service Design di SMA Negeri 22 Palembang - Marutha Berlianti Akbar; Tata Sutabri (FKOM UNIKU, 2024)
This research aims to analyze and evaluate the management of new student admission services at SMA Negeri 22 Palembang using the ITIL Version 3 Framework in the Service Design domain. The problems of this research are that there is no connection between the school website and the PPDB Online application owned by the government, and there is a decrease in bandwidth when using the application together when registration is carried out for new students. This research uses a qualitative method by collecting data techniques through interviews, observation, and analysis. The results showed that the application of ITIL in the management of new student admission services can improve the efficiency and quality of services ensuring the fulfillment of the needs of prospective students and parents, as well as strengthening the relationship between schools and communities around Talang Kelapa Palembang. The conclusion of this research is that the use of ITIL in the management of new student admission services at SMA Negeri 22 Palembang can provide benefits for SMA Negeri 22 Palembang to improve services for new student admissions, and it has a positive impact on the community's view of SMA Negeri 22 Palembang.